‘Vastu Shastra’- An Important Aspect Of Culture And Heritage In The Design And Planning Of Sustainable Cities - Bhanushali, Sulakshana; Nene, Supriya (MAJ - Malaysia Architectural Journal, 2025)
The UN Brundtland Commission first defined sustainability, in the year 1987, as “meeting the needs of the present without compromising the ability of future generations to meet their own needs”, by endeavours and initiatives towards the preservation of a particular resource, natural or otherwise. In recent times, preservation of Cultural Heritage and in particular, Architectural Cultural Heritage has come into light as an important aspect of planning for cities of the future. ‘Smart cities’ in particular, foray into the technological and digital aspects of city infrastructure. The traditional Indian Knowledge System of ‘Vastu-Shastra’ has been ignored in this context, where western philosophies and theories in planning and design have become a popular norm. This paper will highlight the ancient wisdom of ‘Vastu-Shastra’ as Architectural Cultural Heritage of the Indian sub-continent and the need for its cognizance as an important aspect in the design and planning of sustainable cities. It will examine the four pillars of sustainability from the lens of the of ‘Vastu-Shastra’ and try to establish its contribution to the future of cities in the context of ‘Sustainable Development Goals’, citing through historical examples of city/town planning, and highlighting the various practices of sustainability embedded as culture and heritage. Thereby, one can see that ‘Vastu-Shastra’ is, by its application through historical times in planning and design in the Indian sub-continent as well as the South-east Asian region and therefore, by virtue of preservation of environment through diligent use of climate and regional response, has a strong connection to the historical and cultural aspect of the society. This makes it an integral part of the ACH of the Indian sub-continent and South-east Asian region and an important consideration for the future cities from the sustainability aspect as well as cultural heritage.